Structural Explorations of NCp7–Nucleic Acid Complexes Give Keys to Decipher the Binding Process. Issue 10 (3rd May 2019) - Retureau, Romain; Oguey, Christophe; Mauffret, Olivier; Hartmann, Brigitte
Abstract: A comprehensive view of all the structural aspects related to NCp7 is essential to understand how this protein, crucial in many steps of the HIV-1 cycle, binds and anneals nucleic acids (NAs), mainly thanks to two zinc fingers, ZF1 and ZF2. Here, we inspected the structural properties of the available experimental models of NCp7 bound to either DNA or RNA molecules, or free of ligand. Our analyses included the characterization of the relative positioning of ZF1 and ZF2, accessibility measurements and the exhaustive, quantitative mapping of the contacts between amino acids and nucleotides by a recent tessellation method, VLDM. This approach unveiled the intimate connection between NA binding process and the conformations explored by the free protein. It also provided new insights into the functional specializations of ZF1 and ZF2. The larger accessibility of ZF2 in free NCp7 and the consistency of the ZF2/NA interface in different models and conditions give ZF2 the lead of the binding process. ZF1 contributes to stabilize the complexes through various organizations of the ZF1/NA interface. This work outcome is a global binding scheme of NCp7 to DNA and RNA, and an example of how protein–NA complexes are stabilized. Graphical Abstract: Unlabelled Image Highlights: Crucial in the HIV-1 cycle, NCp7 binds and anneals nucleic acids (NAs). The NCp7–NA binding process exploits a set of free NCp7 dynamical conformations. From accessibility and interface analyses, ZF2 initiates the binding to NA. ZF1 stabilizes the complexes through various interface organizations. Additional outcome: an example of how protein–NA complexes are stabilized.